2005
DOI: 10.1111/j.1468-8123.2005.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Textural and isotopic evidence on the fluid source and transport mechanism of antitaxial fibrous microstructures from the Alps and the Appalachians

Abstract: The source of fluid-forming veins is of great importance in order to understand the hydraulic system acting in the earth's crust. The study of syntectonic antitaxial veins is one of the few methods by which the opening history can be deduced from rocks, and thus these veins are of primary importance in determining rock kinematics. Antitaxial veins were taken from black shales in two different tectonic settings in the Helvetic Alps, Switzerland, and the Taconic Appalachians, New York State. These syntectonic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 53 publications
(86 reference statements)
0
33
0
Order By: Relevance
“…The texture of younger V1 veins suggests the transport of fluid along an open fracture resulting in a blocky vein microstructure combined with a decrease of growth rate and increase of the grain size towards the center of the vein (Hilgers et al 2004;Hilgers & Sindern 2005). The observed orientation of veins corresponds to the major system of faults in this area that formed during the Late Miocene ( Fig.…”
Section: The Growth Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…The texture of younger V1 veins suggests the transport of fluid along an open fracture resulting in a blocky vein microstructure combined with a decrease of growth rate and increase of the grain size towards the center of the vein (Hilgers et al 2004;Hilgers & Sindern 2005). The observed orientation of veins corresponds to the major system of faults in this area that formed during the Late Miocene ( Fig.…”
Section: The Growth Mechanismmentioning
confidence: 99%
“…The regular course of older composite V2 vein suggests that the vein formation was initiated by brittle fracturing of rock (Cosgrove 1993;Hilgers & Sindern 2005). The tension veins initially formed parallel to the maximum shortening direction which corresponds to the direction of the vein (Bons 2000).…”
Section: The Growth Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…advective, fracture-channelised-flow versus percolation through the host rock) have been brought into focus (Bons 2000;Hilgers & Urai 2002a). Hilgers & Sindern (2005) and Barker et al (2006) combined stable-isotope data with radiogenic isotopes (Sr 87 ⁄ Sr 86 ) and trace and rare earth elements to resolve the fluid source and flow path of antitaxial vein parent fluids. Rye & Bradbury (1988) found that vein calcites with the same fluid source but different textures display different isotope compositions.…”
Section: Introductionmentioning
confidence: 99%
“…Applications include assessment of fluid-rock interaction (Hilgers & Sindern 2005) and the evolution of mineralising fluids during fluid-rock interaction (Cox 2007). Bottomley & Veizer (1992) and Rye & Bradbury (1988) assessed recrystallisation of a pre-existing vein system and fluid-rock interaction during nappe stacking, respectively.…”
Section: Introductionmentioning
confidence: 99%